Service Facet Prioritisation Using Grey Relation Approach. (September 2016) - Verma, Sanjeev; Prasad, Ram Komal
This article attempts to find the relative importance of various service attributes having significant influence on student's choice set for selection of management institutes. Relative importance of service attributes in management education is evaluated and graded with the help of grey relational analysis. The result of the study indicates that management education institutions must reconsider service strategy in view of the return that specific action provides. Data revealed that tangibles and directly felt service attributes such as academic aspects, attitude and assurance are more important areas to be focused. Grey areas like non-academic aspects and spend on brand building does not receive much importance and resources may be realigned to fetch better results. The findings of the study would help the promoters of institutions and academicians to take right initiatives for ensuring the service quality of management education.